Characterization of Pyrolytic Sugars in Bio-Oil Produced from Biomass Fast Pyrolysis - Yu, Yun; Chua, Yee Wen; Wu, Hongwei (American Chemical Society, 2016)
This study characterizes the pyrolytic sugars in three bio-oils (with a total sugar content range of 55.6–69.2 mg g–1 bio-oil) produced from biomass fast pyrolysis by high performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) and two-dimensional 1H–13C heteronuclear single-quantum correlation–nuclear magnetic resonance (HSQC-NMR). Depending on bio-oil sample, glucose (mainly derived from cellulose) contributes ~67–79 wt % of total pyrolytic sugars in the bio-oil, and the rest of the sugars are derived from hemicellulose. The majority (>96%) of pyrolytic sugars are present in the water-soluble fraction of bio-oil, mainly in the form of cellulose-derived anhydrosugars such as levoglucosan and cellobiosan. A small portion of hemicellulose-derived sugar structures are also found in the water-soluble fraction of bio-oil. Unlike six-carbon sugars (glucose, galactose, and mannose) which are mainly present as anhydrosugars (i.e., ~ 79–86% on a carbon basis for glucose), a large portion of five-carbon sugars (xylose and arabinose) in the water-soluble fraction of bio-oil are present as monomer sugars (i.e., ~ 24–39% on a carbon basis for arabinose and ~32–42% on a carbon basis for xylose). The results suggest that the formation of anhydrosugars from hemicellulose pyrolysis is difficult for five-carbon sugars and the hydrolysis of hemicellulose can be catalyzed by the organic acids produced during pyrolysis. A minor portion (<4%) of sugar structures also exists in the water-insoluble fraction of bio-oil, possibly formed via thermal ejection mechanism from hemicellulose components connected to lignin structures.